Reciprocating Probe Measurements of L-H Transition in LHCD H-Mode on EAST - 刘鹏 徐国盛 汪惠乾 蒋敏 王亮 张炜 刘少承 颜宁 丁斯晔 (Plasma science & technology, 2013)
As the power available in the initial phase of the ITER operation will be limited, accessing the high confinement mode （H-mode） with low heating power will be a critical issue. In the recent experiment on EAST, the H-mode was obtained for the first time with lower hybrid current drive （LHCD） wave only. Reciprocating Langmuir probe measurements at the outer midplane showed that the electron density ne and electron tempel：ature Te in the scrape-off layer （SOL） were significantly reduced in the ELM-free phase, resulting in the increase of lower-hybrid wave （LHW） reflection. It was found that the power loss Ploss was comparable during the L-H transition, by comparing the adjacent L-mode and H-mode discharge. The Da emission, Te and ne decreased rapidly in the time scale of about 1 ms, and the radial electric field Er turned positive in this process near the last closed flux surface. Multiple L-H-L transitions were observed during a single shot when the applied LHW power was marginal to the threshold. The floating potential （Vf） had negative spikes corresponding with the Da signal, and Er oscillation evolved into several intermittent negative spikes just before the L-H transition. In some shots, dithering was observed just before the L-H transition.